Problematika Perkawinan Dini dalam Sistem Hukum Keluarga Islam di Indonesia - Nurmilasari; Kurniati; Musyfikah Ilyas (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The novelty of this study lies in its comprehensive analysis of early marriage practices within the Islamic family law system in Indonesia through the maqāṣid al-syarī‘ah approach. This research does not merely discuss the causal factors and impacts of early marriage, but also examines the gap between positive legal norms, social realities, and religious understanding within society. Unlike previous studies that generally focus only on social aspects or legal regulations, this study integrates the perspectives of Islamic law and positive law in assessing early marriage practices in a more contextual and multidimensional manner. Furthermore, this study offers a contextual reinterpretation of Islamic law through the maqāṣid al-syarī‘ah approach by emphasizing that maturity in marriage should not be measured solely from a biological perspective, but must also include psychological, social, educational, and economic readiness. This research also positions child protection, gender justice, and societal welfare as the primary objectives in addressing early marriage practices. Another novelty of this research lies in its proposal to strengthen the mechanism of marriage dispensation granted by judges through stricter approval requirements, including considerations of psychological readiness, health conditions, educational continuity, and the social circumstances of the child. In addition, this study emphasizes the importance of implementing legal sanctions against violations of the minimum marriage age regulation as a form of preventive child protection. Therefore, this research contributes not only theoretically to the development of Islamic family law, but also practically by offering solutions for controlling early marriage practices in Indonesia.